Strategi Pengembangan Sumber Daya Manusia yang Kompetitif pada Toko Roti Helen Cempaka - Maria Rasdiana Bure; Yosefin Vitrian Nona Tresna; Maria Olgantina Lue; Camelia Indriani Trisanty Lodan; Maria Imelda Dua Ate; Trifonia Sumelan Loru (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
Human resources (HR) are an important factor in determining the success of a business because they play a role in increasing productivity, service quality, and company competitiveness. In an era of increasingly intense business competition, companies are required to have a competitive, professional workforce that is capable of adapting to technological developments and customer needs. This paper aims to identify competitive human resource development strategies at Helen Cempaka Bakery and their impact on business progress. The method used in this paper is a descriptive method with a literature study approach and observation of the business conditions at Helen Cempaka Bakery. The results of the discussion show that human resource development strategies at Helen Cempaka Bakery are implemented through job training, guidance and supervision, motivation, improvement of work discipline, teamwork development, and the use of modern technology and equipment. In addition, indicators of competitive human resources include ability, expertise, knowledge, and good work attitudes. Human resource development has a positive impact on improving employee performance quality, business productivity, service quality, and customer satisfaction. Therefore, continuous human resource development is highly necessary so that Helen Cempaka Bakery can maintain competitiveness and continue to grow amid business competition.